1983
DOI: 10.1093/ajcn/37.4.595
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the resting metabolic rate in obese patients

Abstract: Resting metabolic rate (RMR) was measured in 154 women and 48 men before the beginning of a weight reduction program. In both sexes there were significant univariate correlations between RMR and fat-free mass, body fat, weight, fat cell weight, and fat cell number (from total body water). Women also showed significant correlations between RMR and fat cell number (from total body potassium), free triiodothyronine index, and fasting and postglucose insulin levels. Multiple regression analysis showed that both fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
95
1
9

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(114 citation statements)
references
References 21 publications
9
95
1
9
Order By: Relevance
“…During the hot dry season, we found no relationship between RMR and T 3 levels. Similarly, several studies on humans failed to find an association between circulating concentrations of T 3 and either BMR or RMR (Bernstein et al, 1983;Johnstone et al, 2005). Likewise, there was no correlation between T 3 levels and RMR in Arabian oryx (Oryx leucoryx) during the summer, when food and water were restricted (Ostrowski et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the hot dry season, we found no relationship between RMR and T 3 levels. Similarly, several studies on humans failed to find an association between circulating concentrations of T 3 and either BMR or RMR (Bernstein et al, 1983;Johnstone et al, 2005). Likewise, there was no correlation between T 3 levels and RMR in Arabian oryx (Oryx leucoryx) during the summer, when food and water were restricted (Ostrowski et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a positive relationship between thyroid hormone levels and metabolic rate has been found in captive reptiles (Joos and John-Alder, 1990), birds (Vézina et al, 2009) and mammals (Banta and Holcombe, 2002;Brinkmann et al, 2016;Li et al, 2010), including humans (reviewed in Hulbert, 2000;Kim, 2008). In contrast, other studies report no relationship between metabolic rate and thyroid hormones in captive mammals (Nilssen et al, 1984;Ostrowski et al, 2006), including humans (Bernstein et al, 1983;Johnstone et al, 2005). However, little information is available concerning the relationship between thyroid hormones and metabolic rate for animals living under natural conditions (exceptions are studies on birds: Chastel et al, 2003;Elliott et al, 2013;Welcker et al, 2013;Zheng et al, 2014; and a study of free-ranging Arctic ground squirrels Urocitellus parryii; Wilsterman et al, 2015), and the reported results are ambivalent.…”
Section: Introductionmentioning
confidence: 99%
“…In the present analysis, both FFM and fat mass were predictors of REE. It has been suggested that a contribution from FM to REE only becomes appreciable when relative FM increases above normal, 1,3,20 eg in obese women. It seems more likely that the effect, being relatively small, is more readily detected with the inclusion of individuals with a wide range of body fat.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial portion of the variance of BMR among individuals is explained by body size (including FFM), age, and sex (4)(5)(6)(7)(8). Studies of families (6) and comparisons of mono-and dizygotic twins (9) suggest that BMR is at least in part genetically determined.…”
mentioning
confidence: 99%